2021
DOI: 10.1097/md.0000000000024428
|View full text |Cite
|
Sign up to set email alerts
|

Hospital anxiety and depression scale exhibits good consistency but shorter assessment time than Zung self-rating anxiety/depression scale for evaluating anxiety/depression in non-small cell lung cancer

Abstract: This study aimed to compare Zung self-rating anxiety/depression scale (SAS/SDS) and hospital anxiety and depression scale (HADS) regarding the detection rate, detection consistency, and time of assessment in non-small cell lung cancer (NSCLC) patients. Totally 290 NSCLC patients who underwent surgical resection were consecutively recruited and clinical data of patients were collected. Patients’ anxiety and depression were assessed using HADS and SAS/SDS when they were discharged from hospital and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“… 65 Moreover, HADS could be a better option for depression assessment than SDS in patients with lung cancer. 66 The State‐Trait Anxiety Inventory (STAI) is a self‐report measure of the severity of anxiety symptoms; HADS screens for clinically significant symptoms of anxiety in patients with medical conditions. 67 Taken together, these different scales may have an impact on the detection of depression or anxiety in patients with cancer, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Moreover, HADS could be a better option for depression assessment than SDS in patients with lung cancer. 66 The State‐Trait Anxiety Inventory (STAI) is a self‐report measure of the severity of anxiety symptoms; HADS screens for clinically significant symptoms of anxiety in patients with medical conditions. 67 Taken together, these different scales may have an impact on the detection of depression or anxiety in patients with cancer, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with the above-mentioned different SQ was respectively counted and the proportion was calculated. Comparison of adverse psychological response [ 14 ]: the study employed the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) in the hospital. It showed that the score rose in accordance with the degree of seriousness of adverse psychological response.…”
Section: Methodsmentioning
confidence: 99%
“…e number of patients with the above-mentioned different SQ was respectively counted and the proportion was calculated. (5) Comparison of adverse psychological response [14]:…”
Section: Exclusion Criteria (1) Ose With Lymph Node Metastasis or Ven...mentioning
confidence: 99%
“…The severity of depressive symptoms is defined as <53, no depressive symptoms; 53 to 62, mild depressive symptoms; 63 to 72, moderate depressive symptoms; and 72 to 100, severe depressive symptoms. 20 …”
Section: Methodsmentioning
confidence: 99%